(untitled) (CIPEEX, 2024)
SOCIAL ACTIONS IN DENTISTRY PLAY A CRUCIAL ROLE IN PROMOTING ORAL HEALTH, IMPROVING QUALITY OF LIFE, AND ADVANCING HEALTH EQUITY WITHIN COMMUNITIES AND AMONG INDIVIDUALS. THE OBJECTIVE OF THE PRESENT WORK IS TO REPORT ON THE EXPERIENCE OF A SOCIAL ACTION FOCUSED ON THE FIELD OF MINOR ORAL SURGERY. THE ACADEMIC LEAGUE OF DIAGNOSIS AND ORAL SURGERY (LADCO) - DR. SATIRO WATANABE - CONDUCTED A HIGHLY RELEVANT EXTENSION PROJECT TITLED "ORAL HEALTH FOR ALL," IN COLLABORATION WITH THE MUNICIPAL GOVERNMENT OF ABADINIA. THIS INITIATIVE FOCUSED ON SURGICAL CARE, PARTICULARLY EXTRACTIONS. THE ACTION COMPRISED THREE ESSENTIAL STAGES: SCREENING BY THE MUNICIPAL GOVERNMENT TO IDENTIFY PATIENTS WITH THE PROFILE AND NEED FOR EXTRACTIONS AND THE EVALUATION OF ORAL LESIONS, FOLLOWED BY TWO DAYS OF CARE PROVIDED BY LADCO ON MAY 6, 2023, AND JUNE 24, 2023. DURING THE FIRST DAY OF CARE, A GROUP CONSISTING OF SEVENTEEN STUDENTS AND ONE PROFESSOR DEDICATED THEMSELVES TO THE CARE OF 15 PATIENTS, PERFORMING TEN MODERATELY COMPLEX SURGICAL PROCEDURES. ON THE SECOND DAY, THE TEAM INCLUDED THIRTEEN STUDENTS AND THREE PROFESSORS, WHO ATTENDED TO ELEVEN PATIENTS AND PERFORMED NINE SURGERIES. THIS APPROACH PROVED TO BE ESSENTIAL IN PROMOTING COMPREHENSIVE AND MULTIDIMENSIONAL LEARNING IN SURGICAL DISCIPLINES BY INVOLVING STUDENTS FROM VARIOUS SEMESTERS, THUS ENCOURAGING BOTH HORIZONTAL AND VERTICAL LEARNING WITHIN THESE DISCIPLINES. THE LADCO FACULTY ADVISOR EMPHASIZES THE UNIQUE IMPORTANCE OF THIS PHILANTHROPIC INITIATIVE, RECOGNIZING IT AS A VALUABLE MEANS FOR THE PROFESSIONAL AND PERSONAL GROWTH OF STUDENTS, AS WELL AS FOR PROMOTING COLLABORATION AND INTEGRATION AMONG LEAGUE MEMBERS. THIS TYPE OF EXTENSION SOCIAL ACTION EXEMPLIFIES THE SOCIAL COMMITMENT OF THE ACADEMIC LEAGUE AND ITS POSITIVE IMPACT ON COMMUNITY ORAL HEALTH, GOING BEYOND CONVENTIONAL TEACHING AND EXPANDING THE TRAINING OF FUTURE DENTAL PROFESSIONALS.